Are workplace interventions to reduce sitting effective? A systematic review - Chau, J.; Van Der Ploeg, H.; van Uffelen, J.; Wong, J.; Riphagen, I.; Healy, Genevieve; Gilson, N.; Dunstan, D.; Bauman, A.; Owen, N.; Brown, W. (Elsevier BV, 2010)
Objective: To systematically review the effectiveness of workplace interventions for reducing sitting. Methods: Studies published up to April 2009 were identified by literature searches in multiple databases. Studies were included if they were interventions to increase energy expenditure (increase physical activity or decrease sitting); were conducted in a workplace setting; and specifically measured sitting as a primary or secondary outcome. Two independent reviewers assessed methodological quality of the included studies, and data on study design, sample, measures of sitting, intervention and results were extracted. Results: Six studies met the inclusion criteria (five randomised trials and one pre-post study). The primary aim of all six was to increase physical activity; all had reducing sitting as a secondary aim. All used self-report measures of sitting; one specifically assessed occupational sitting time; the others used measures of general sitting. No studies showed that sitting decreased significantly in the intervention group, compared with a control or comparison group. Conclusion: Currently, there is a dearth of evidence on the effectiveness of workplace interventions for reducing sitting. In light of the growing body of evidence that prolonged sitting is negatively associated with health, this highlights a gap in the scientific literature that needs to be addressed. © 2010 Elsevier Inc.